Computer fundamentals II : a reference manual - Lansigan, Rolando; Gatus, Marivic M.; Geronimo, Sheila M.; San Diego, Bernadette E.; Francisco, Ma. Teresa P.; Simbillo, Lilian Q.; Pasilan, Amelia P. ([Place of publication not identified] [Name of publisher not identified], 2003)
Computer fundamentals II a reference manual focuses on three outstanding and in demand applications: Html, Microsoft PowerPoint and Microsoft Access and Computer Ethics .
Chapter1. Computer Ethics -- Chapter2. HTML (Hypertext Markup Language) -- Chapter3. Introduction to Microsoft PowerPoint -- Chapter4. PowerPoint basics -- Chapter5. Getting Started in PowerPoint -- chapter6. Working with Slides -- Adding and formatting Text -- Chapter8. Drawing and Working with Objects -- Chapter9. Adding Clip Art and Other Pictures -- Chapter10. Making Global Changes -- Chapter11. designing Electronic Slide Show -- Chapter12. Printing Presentation -- Chapter13. Introduction to Microsoft Access -- Chapter14. MS- Access Basics -- Chapter15. Working with Tables -- Chapter16. Forms, Query and Report .
Keywords: INFORMATION TECHNOLOGY; COMPUTER; MANUAL